Can Post-Grant Reviews Improve Patent System Design? A Twin Study of US and European Patents - Stuart J.H. Graham; Dietmar Harhoff (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
This paper assesses the impact of adopting a post-grant review institution in the US patent system by comparing the 'opposition careers' of European Patent Office (EPO) equivalents of litigated US patents to those of a control group of EPO patents. We demonstrate several novel methods of twinning US and European patents and investigate the implications of employing these different methods in our data analysis. We find that EPO equivalents of US litigated patent applications are more likely to be awarded EPO patent protection than are equivalents of unlitigated patents, and the opposition rate for EPO equivalents of US litigated patents is about three times higher than for equivalents of unlitigated patents. Patents attacked under European opposition are shown to be either revoked completely or narrowed in about 70 percent of all cases. For EPO equivalents of US litigated patents, the appeal rate against opposition outcomes is considerably higher than for control-group patents. Based on our estimates, we calculate a range of net welfare benefits that would accrue from adopting a post-grant review system. Our results provide strong evidence that the United States could benefit substantially from adopting an administrative post-grant patent review, provided that the post-grant mechanism is not too costly.
urn:nbn:de:bvb:19-epub-13510-2
Keywords: K41; K11; L10; 330; patent system; post-grant review; opposition; litigation